JASMIN, M.G.; FRERES Jr., J (Org). História dos conceitos: debates e perspectivas. Rio de Janeiro: Editora PUC - Rio; Loyola. IUPERJ, 2006. 174 p. - Roiz, Diogo da Silva (Educação e Filosofia, 2010)
RESENHA